Heterogeneity in outcome assessment for inflammatory bowel disease in routine clinical practice: a mixed-methods study in a sample of English hospitals. Issue 12 (30th December 2021) - Razanskaite, Violeta; Kallis, Constantinos; Young, Bridget; Williamson, Paula R; Bodger, Keith
Abstract : Objectives: Knowledge of the extent of variation in outcome assessment for inflammatory bowel disease (IBD) in routine practice is limited. We aimed to describe and quantify variation in outcome coverage and to explore patient, clinician and practitioner factors associated with it. Design: Prospective exploratory mixed-methods study. Setting: IBD clinics at six hospitals in North West England with differing electronic health record (EHR) systems. Methods: Mixed-methods study comprising: (a) structured observations of outcomes elicited during consultations (102 patients consulting 24 clinicians); (b) retrospective analysis of outcomes recorded in the EHR (909 consultations; 127 clinicians) and (c) semistructured interviews with the 24 observed clinicians. We determined whether specific outcome 'sets' were elicited or recorded, including: (1) a minimum set of symptom pairs ('PRO-2'); (2) symptom sets from disease activity indices and (3) a reference list of 37 symptoms, signs and impacts. Factors associated with variation were explored in univariate and multivariate binary logistic regression analyses and from clinician interviews. Results: PRO-2 coverage was not invariable (elicited during 81% of observed consultations; recorded in 56% of EHR) and infrequent for complete activity indices (all domains from Harvey-Bradshaw Index: elicited, 18%; recorded, 5%). The median number of outcomes from the reference list elicited per consultation was 12 (13-fold variation) and recorded in EHR was 7 (>20-fold variation). Symptom quantification (PRO-2) seldom adhered closely to standardised descriptors and an explicit timeframe was defined rarely. PRO-2 recording in EHR was associated with a diagnosis of ulcerative colitis (OR: 2.09 (95% CI 1.15 to 3.80)) and nurse-led consultations (OR: 6.98 (95% CI 3.28 to 14.83)) and a three-way model suggested 26% of total variability lay between clinicians, 17% between patients but the remainder was unexplained. Most clinicians expressed preference for individualised health status evaluations versus standardised outcome assessments. Conclusions: There was little evidence for standardised assessment and recording of IBD outcomes and substantial intra-clinician and inter-clinician variation from one consultation to another. Nurses demonstrated a greater tendency to standardised practice.